A pilot‐scale rotary infrared dryer of shrimp (Metapenaeus affinis): Mathematical modeling and effect on physicochemical attributes. (22nd December 2021) - Al‐Hilphy, Asaad R.; Al‐Mtury, Atheer Abdul Amir; Al‐Iessa, Sajedah A.; Gavahian, Mohsen; Al‐Shatty, Sabah Malik; Jassim, Muhammad Ali; Mohusen, Zainab Abdul Ameer; Mousavi Khaneghah, Amin
Abstract: A new rotary infrared dryer (R.I.D.) was manufactured to dry shrimp ( Metapenaeus affinis ) at 60, 70, and 80°C. Also, mathematical modeling along with artificial neural networks (ANNs) was used for data prediction. The results showed that the exponential proposed model and ANN could be applied to well‐predict the moisture ratio of shrimp. Besides, running R.I.D. at 80°C resulted in the highest reduction in moisture content and saved about 42% of drying time. The thermal efficiency of the R.I.D. at a temperature of 70°C ranged between 83 and 89%, which was about 15% higher than the conventional dryer. The drying rate by both R.I.D. and conventional methods consist of a falling rate period, ranging between 1.68 × 10 −4 and 0.47 × 10 −4 1/s. Furthermore, the mass transfer coefficient increased by about 104.6% when drying temperature increased from 60 to 80°C. The browning index increased with the increase of drying temperature. Specific energy consumption, browning index, and drying time of rotary infrared system were lower than those of conventional system by 46.9, 33.3, and 34.7%, respectively. R.I.D. reduced energy consumption, decreased the color changes, improved the rehydration ratio, and affected the chemical composition of dried shrimp as compared with the conventional process. Practical Applications: A new rotary infrared dryer was designed and developed and its performance was evaluated with the assistance of artificial neural networks. This system was shown to be energy‐ and time‐saving and capable of producing high‐quality dry shrimp ( Metapenaeus affinis ). Also, the system is simple and affordable due to reducing energy consumption and relatively low cost of components. Therefore, it has the potential to be used in the industry after further economic and technical evaluation.